T-Cell Expression of Angiotensin-Converting Enzyme 2 and Binding of Severe Acute Respiratory Coronavirus 2. (16th December 2021) - Welch, Jennifer L; Xiang, Jinhua; Chang, Qing; Houtman, Jon C D; Stapleton, Jack T
Abstract: The pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is not completely understood. SARS-CoV-2 infection frequently causes significant immune function consequences including reduced T cell numbers and enhanced T cell exhaustion that contribute to disease severity. The extent to which T cell effects are directly mediated through infection or indirectly result from infection of respiratory-associated cells is unclear. We show that primary human T cells express sufficient levels of angiotensin converting enzyme 2 (ACE-2), the SARS-CoV-2 receptor, to mediate viral binding and entry into T cells. We further show that T cells exposed to SARS-CoV-2 particles demonstrate reduced proliferation and apoptosis compared to uninfected controls, indicating that direct interaction of SARS-CoV-2 with T cells may alter T cell growth, activation, and survival. Regulation of T cell activation and/or turnover by SARS-CoV-2 may contribute to impaired T cell function observed in patients with severe disease. Abstract : No specific interaction between SARS-CoV-2 and T-cells is described. SARS-CoV-2 receptor (ACE-2) mRNA and protein were expressed in T-cells, and expression increased following T-cell activation. ACE-2 also mediated SARS-CoV-2 and spike protein entry, resulting in altering T-cell proliferation and apoptosis.